Analysis of the Mitogenomes of Two Helotid Species Provides New Insights into the Phylogenetic Relationship of the Basal Cucujoidea (Insecta: Coleoptera) - Jing Liu; Yuhang Yang; Zihan Yan; Haishan Wang; Ming Bai; Chengmin Shi; Jing Li (Biology, 2023)
Helotid beetles are commonly found in places where sap flows from tree trunks and in crevices in bark. The Helotidae family is a rare and primitive group of Cucujoidea. To date, no complete mitochondrial (mt) genome has been sequenced for this family. To better understand the characteristics of the mt genome and the evolution of Cucujoidea, we sequenced and annotated the complete mt genomes of Helota thoracica (Ritsema, 1895) and Helota yehi Lee, 2017 using next-generation sequencing. These are the first record of Helotidae mt genomes. The RNA secondary structures of both species were also predicted in this study. The mt genomes of H. thoracica and H. yehi are circular, with total lengths of 16,112 bp and 16,401 bp, respectively. After comparing the mt genomes of H. thoracica and H. yehi, we observed the gene arrangement, codon usage patterns, base content, and RNA secondary structures of both species to be similar, which has also been noted in other Coleoptera insects. The nucleotide sequence of the coding regions and the control region has small differences. The phylogenetic analysis indicated that Helotidae and Protocucujidae are sister groups and revealed the relationship between seven families; however, the validity of the two series (Erotylid series and Nitidulid series) as larger groups in the superfamily was not supported. The mt phylogenomic relationships have strong statistical support. Therefore, the division of Cucujoidea into series should be re-examined. Our results will provide a better understanding of the mt genome and phylogeny of Helotidae and Cucujoidea and will provide valuable molecular markers for further genetic studies.